Efeito da indução de predição de erro durante a reconsolidação da memória humana no desempenho de habilidades motoras - Silva, Maristella Borges (2018)
Memory reconsolidation is the process in which a previously consolidated and stable memory can return to a temporary labile state after retrieved, requiring a new stabilization process to persist. During the labile period, the memory trace is susceptible to modification, which provides a potential therapeutic opportunity to introduce interventions to update, weaken or strengthen that memory. However, very little has been researched about the possibility of using interventions during the reconsolidation of human motor memory to enhance motor skill performance. In this sense, the aim of this study was to evaluate the influence of memory reactivation of a motor skill and the use of behavioral interventions during its reconsolidation process on motor performance. Sixty healthy participants learned a new motor task in which they needed to control the movement of a horizontal cursor on the screen by producing isometric lateral pinch strength to reach the center of certain targets. The participants were instructed to move the cursor as accurately and as quickly as possible to perform the task. The experimental paradigm was developed over two consecutive days, with three sessions of data collection. In the first day, sessions 1 and 2 were performed with 6 h difference between them. In the second day, 24 h after session 1, session 3 was performed. Participants were randomized into six different experimental groups. All groups learned the new motor task in session 1 and retested it in session 3. In session 2, there were differences between the experimental groups in relation to two main conditions: the presence or absence of a formal session of memory reactivation composed by the execution of repetitions of the motor task originally learned and the application of different types of intervention (training with the original motor task, slightly modified or moderately modified). The results showed that the use of interventions characterized by a moderate level of task variability during memory reconsolidation improves motor skill performance more than the repetitive practice of the same learned task. These findings confirmed the hypothesis that a behavioral intervention characterized by a moderate variability of the original task induces enough threshold of error detection to promote adjustments in the prediction mechanisms, providing greater strengthening of human motor memory during its reconsolidation and, consequently, greater progress in motor performance. Moreover, there was no significant difference in percentage gain in motor performance between pairs of groups that differed from each other only by the presence or absence of a formal session designed to memory reactivation. The practice of the original motor task or the modified motor task in session 2 induced prediction error during the reactivation of newly acquired motor memory, triggering a process of destabilization-reconsolidation. Contrary to the initial hypothesis, the results indicate that the use of a session exclusively dedicated to memory reactivation, with practice of the originally learned task, is not a determinant condition to destabilize the motor memory, but the induction of prediction error during the reactivation session. The induction of adequate prediction error levels during the process of memory reconsolidation generates greater adjustments in the motor control system and optimizes the updating of the prediction mechanisms, leading to a greater strengthening of motor memory, with consequent progress in the performance of the motor skill.